Mutation status of the mediator complex subunit 12 (MED12) in uterine leiomyomas and concurrent/metachronous multifocal peritoneal smooth muscle nodules (leiomyomatosis peritonealis disseminata) - Rieker, Ralf; Agaimy, Abbas; Moskalev, Evgeny; Hebele, Simone; Hein, Alexander; Mehlhorn, Grit; Beckmann, Matthias; Hartmann, Arndt; Haller, Florian (Pathology, 2013)
Aims: The pathogenesis and classification of multicentric smooth muscle tumours with benign appearance and concurrent/metachronous uterine and peritoneal involvement is controversial and may on occasion be diagnostically challenging. Leiomyomatosis peritonealis disseminata (LPD) is a rare condition affecting women of reproductive age, characterised by the occurrence of multiple small peritoneal smooth muscle nodules with bland histology. Methods: We investigated a total of 12 uterine and seven concurrent/metachronous peritoneal smooth muscle nodules with benign appearance from two females for mutations in the mediator complex subunit 12 (MED12), which has recently been identified as the most frequent genetic aberration in uterine leiomyomas. Results: The first case harboured different MED12 mutations in the peritoneal nodules. Mutational status of peritoneal nodules was discordant with that of the uterine leiomyomas. The second case displayed the same MED12 mutation in all five peritoneal nodules, but this mutation was not detected in her current uterine leiomyomas. Conclusions: Our results suggest that smooth muscle neoplasms with benign appearance of the primary and secondary mü llerian system share a similar genetic background of MED12 mutation in combination with oestrogen dependency. Analysis of MED12 mutation status might be a valuable adjunct tool for the future classification of these sometimes diagnostically challenging multicentric tumours. © 2013 Royal College of Pathologists of Australasia.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Leiomyomatosis peritonealis disseminata; MED12; Uterine leiomyoma